(untitled) (International Journal of Engineering and Computer Science, 2018)
Damages caused by recent earthquakes have pointed out that the seismic behaviour of a structure is highly influenced not only by the response of the super structure but also by the response of the foundation and ground as well. The effect of SSI becomes prominent for heavy structures resting on relatively soft soils. The main focus of the present investigation is to evaluate the seismic performance of the fifteen storey, reinforced concrete building with piled raft foundation using linear time history analysis by finite element based software SAP 2000. The various results such as time period, displacements, base shear and settlements are compared and the effect of piled raft foundation behaviour is evaluated.